What said the way? (Qué dice el camino?) Broadening the concept of education through experiences in opposing ontologies while walking to Santiago - Chris Beeman (FahrenHouse, 2017)
This paper asks the question, is the state of being experienced on the Camino de Santiago de Compostela - «Camino-being» - related to or in some ways compatible with an Indigenous/Autochthonous state of being? At first glance, the two states might appear to share a connection through their focus on the natural environment: the relatively wild spaces of certain arcs of the Camino would certainly seem to link this kind of journey with the ecologically-oriented state of being of Indigeneity/Authochthony. Connection with the natural world is a significant aspect of the pilgrimage for many on the Camino, who perceive that without this spiritual progress could not have occurred. This study uses a hermeneutic approach to investigate these ideas as encountered in pilgrimage on the Camino. The central question also leads to some related, and more directly educational ones: Despite the apparent or actual relatedness, does the circumstance of being in wild places influence the learning that occurs therein, and how might a consideration around such learning influence educational practice?